Methicillin-resistant staphylococcus aureus carriage and comorbidity in patients with chronic kidney disease V D stage: a 3-year prospective study - Shifris, I. (Ukrainian Journal of Nephrology and Dialysis, 2020)
Asymptomatic methicillin-resistant Staphylococcus aureus (MRSA) nasal colonization is a confirmed factor that affects the frequency of comorbid bacterial infections and mortality in patients with end-stage renal disease (ESRD). The aim was to study the frequency of comorbid conditions and their dynamics in ESRD patients depending on their MRSA status. Methods. To prospective cohort study included 265 ESRD patients, 204 of whom were treated by hemodialysis (HD) and 61 by peritoneal dialysis (PD). All recorded comorbidities, their frequency and the dynamics of change, polymorbidity indices, were analyzed depending on whom had MRSA nasal colonization (group 1, n = 92) and without it (group 2, n= 173). The most common cause of ESRD was glomerulonephritis - 161 patients (60.75%). The groups were representative according to gender, age, type of kidney injury and modality of renal replacement therapy (RRT). Results. According to the results of a 3-year study investigation, the patients with MRSA carriage had a statistically significant higher level of comorbid conditions frequencies compared to the patients who had opportunistic pathogenic bacteria carriage, namely: prevalence of coronary artery disease (55.4% vs 30.1%, р=0.0001), heart failure (44.6% vs 25.4%, р=0.0015), secondary hyperparathyroidism (61.9% vs 45.1%, р=0,009), chronic obstructive pulmonary disease (31.5% vs 17.3%, р=0.0082), peripheral vascular disease (39.15 vs 17.9%, р=0.0001). The increase in the modified polymorphism index in patients of Group 1 and Group 2 during the observation period, was 30 % and 5% respectively. One hundred thirty three hospitalization cases were detected during follow-up period: among patients from Group 1- 66 (71.34%) cases, Group 2 - 67 (38.73%); χ² = 26.180, р < 0.0001; RR – 1.8524, 95% ДІ: 1.4760 – 2.3247. Conclusions. Asymptomatic MRSA nasal colonization is a factor that can increase the incidence of coexisting diseases as well as the total number of comorbid conditions in dialysis patients.